(untitled) (LACCEI, 2024)
In the face of the pandemic, the Chair of Probability and Statistics of the National Polytechnic School implemented online teaching. In the present work, the academic performance of the students of the subject is analyzed during the semesters 2019-A and 2019 - B in face-to-face mode, in comparison with the semesters 2020-A, 2020-B, 2021-A, 2021-B and 2022-A in online mode. For this, the final grades obtained by the students were considered and an analysis of the variances was carried out for the semesters considered using the Levene test and later an ANOVA analysis, the methodological adaptation parameters in each semester were considered only in the study. It was identified that the averages of the final grade are close in all the semesters, but the dispersion and outliers are visibly different, when verifying the homogeneity of the variances using the Levene test, the result was that these are not homogeneous, later the one-way ANOVA test was carried out, in which it was determined that there is a significant difference in at least a couple of periods and these are different from each other with 95% confidence Tests were carried out for pairs of periods and similarities were determined between the semesters in virtual modality, the density functions show similarities between the types of modalities with the exception of semesters 2020-A and 2022-A, which present a markedly different behavior.